Lending standards, credit booms and monetary policy - Elena Afanasyeva; Jochen Güntner (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2014)
This paper investigates the risk channel of monetary policy on the asset side of banks' balance sheets. We use a factoraugmented vector autoregression (FAVAR) model to show that aggregate lending standards of U.S. banks, such as their collateral requirements for firms, are significantly loosened in response to an unexpected decrease in the Federal Funds rate. Based on this evidence, we reformulate the costly state verification (CSV) contract to allow for an active financial intermediary, embed it in a New Keynesian dynamic stochastic general equilibrium (DSGE) model, and show that - consistent with our empirical findings - an expansionary monetary policy shock implies a temporary increase in bank lending relative to borrower collateral. In the model, this is accompanied by a higher default rate of borrowers.
urn:nbn:de:hebis:30:3-361011
Keywords: E44; E52; 330; Bank lending standards; Credit supply; Monetary policy; Risk channel